Ethanol production from oil palm empty fruit bunch by simultaneous saccharification and fermentation (SSF) with kluyveromyces marxianus and saccharomyces cerevisiae - Suwanan Sukhang (Prince of Songkla University, 2023)
Master of Engineering (Chemical Engineering), 2019